Strain and tilt during epitaxial growth of highly ordered In2O3 nanorods. - Regoutz, A; Egdell, R; Wermeille, D; Cowley, R; Zhang, K (2013)
Precise control over the morphology of one-dimensional (1D) nanostructures is an essential step in the effort to develop nano-devices with exotic properties. Here we demonstrate the formation of highly aligned In2O3 nanorod arrays on Y-stabilised ZrO2(110) grown by oxygen plasma assisted molecular beam epitaxy. The evolution of morphologies, strain and tilt in the In2O3 nanorods are studied by atomic force microscopy and high resolution synchrotron-based X-ray diffraction. It is shown that the preferential 1D growth is driven by minimization of the total surface and interface energies. The mismatch of ca. 1.7% between the substrate and the epilayer is accommodated by strain along the [110] direction coupled with tilting of the rods along [001] and [001] directions and contraction in the [110] direction. The present highly ordered In2O3 nanorod arrays supported on an insulating substrate are of potential interest for large-scale fabrication of nano-devices.